Médecine autochtone sud-africaine (muti) et innovation biopharmaceutique : connaître l'umhlonyane - Laplante, Julie (Anthropologica, 2014)
The medicinal plant umhlonyane or Artemisia afra (Jaqu. Ex. Willd.) is currently under examination by the preclinical trial in Cape Town, South Africa. The objective is to determine its efficacy at the biomolecular level in order to find a cure against the tuberculosis pandemic. In parallel, the trial aims to recognize indigenous knowledge hinting at its therapeutic potential. I thus aim to understand how scientists, indigenous healer-diviners and herbalists collaborate and con ciliate their respective approaches which distinguish them selves in the ontologies they bring into being.